Capillary bundle model for gravitational flow of emulsion through granular media and experimental validation. (22nd November 2016) - Błaszczyk, Mariola M.; Sęk, Jerzy P.; Przybysz, Łukasz
Abstract: Emulsion flow in porous systems is different from the flow of the individual phases, because there are different mechanisms that must be taken into account when modeling the movement of such liquids. In the literature, there are no mathematical models which take into account phenomena characterizing such flows. The development of such dependence would allow for substantial improvements on the assessment of contamination and facilitate the selection of appropriate methods of soil and groundwater remediation. In this paper a numerical model, describing the process of gravitational flow of the emulsion through the porous structures, has been developed. Using this model, it was possible to predict the flow rate of fluid through the bed, and changes in the emulsion structure. This model was based on the concept of capillary bundles and assumed conversion of granular deposit into a network of capillaries. The calculation results obtained using the proposed model were compared with the results of own experimental works and high accordance was achieved. Highlights: The model of the gravitational flow of emulsion through granular bed was developed. Dimensions of the bed, grain size distribution, properties of media were considered. Unsteady character of flow were taken into account. Emulsion concentration changes and retaining of droplets in the bed was predicted. The carried out experiments confirmed the applicability of the numerical model.